Study on the diffusion mechanism of gangue slurry within the rough connected voids in the caving zone - Jiaqi Wang; Wenbing Fan; Rui Gao; Qiang Zhang; Peng Huang (Scientific Reports)
Abstract Grouting and filling in the caving zone is one of the optimal methods for disposing of gangue. Unraveling the diffusion pattern of gangue slurry is pivotal for precise grouting control and enhancing gangue disposal capacity. To investigate the impact mechanism of roughness, void aperture, and grouting pressure on the diffusion pattern of gangue slurry within the caving zone, a three-dimensional model featuring roughly connected voids was developed using numerical simulation. This analysis encompassed the diffusion radius, velocity, contour, and diffusion pressure of gangue slurry across varying factor levels. Additionally, a slurry flow force balance model within the void micro-segment was constructed to validate the simulation outcomes. The findings reveal that the diffusion radius and velocity are influenced by roughness, void aperture, and grouting pressure, whereas the diffusion contour is shaped by roughness and void aperture. Specifically, roughness spectral exponent influences slurry diffusion by impacting the filling space, void aperture modifies slurry diffusion by altering the resistance along the path, and grouting pressure affects slurry diffusion through its influence on the total head. Notably, grouting pressure exerts a stable and consistent influence on gangue slurry filling.